Akad Dalam Sepakat: Akuntansi Bagi Hasil Nelayan Desa Campurejo - Mohammad Ilham Galang Pratama; Tumirin Tumirin (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine the implementation of profit-sharing agreements among fishermen in Campurejo Village. Profit-sharing among fishermen is an agreement made by two or more parties with the shared goal of utilizing capital to generate profits. Profit-sharing has been practiced by Indonesian society for a long time, with its implementation usually carried out verbally without clear documentation. Another issue arising from profit-sharing is the limited access to capital sources for the majority of fishermen. This study uses a qualitative approach with an ethnomethodology method, and data collection techniques include documentation, interviews, and observation. Interviews were conducted with the